2022
DOI: 10.1021/acs.est.2c03828
|View full text |Cite
|
Sign up to set email alerts
|

Elucidating the Differences in Metal Toxicity by Quantitative Adverse Outcome Pathways

Abstract: Numerous studies have reported that the toxicity differences among metals are widespread; however, little is known about the mechanism of differences in metal toxicity to aquatic organisms due to the lack of quantitative understanding of their adverse outcome pathway. Here, we investigated the effects of Cd and Cu on bioaccumulation, gene expression, physiological responses, and apical effects in zebrafish larvae. RNA sequencing was conducted to provide supplementary mechanistic information for the effects of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 71 publications
0
7
0
Order By: Relevance
“…Among all DEGs, the interleukin 1, β ( il1b ) gene was selected as a candidate because it is one of the common DEGs (Figure H) and has high expression levels among all DEGs (Figure S6). In addition, il1b is one of the significant genes reported to be involved in many metals’ toxicity , and showed a good dose–response relationship with mortality in our previous study . Another advantage is that for complex mixtures exposed to natural environments, it might be easier to determine one or a set of genes than to determine the internal residues of each mixture component, especially with the development of high-throughput genetic detection technologies. , …”
Section: Resultsmentioning
confidence: 83%
See 3 more Smart Citations
“…Among all DEGs, the interleukin 1, β ( il1b ) gene was selected as a candidate because it is one of the common DEGs (Figure H) and has high expression levels among all DEGs (Figure S6). In addition, il1b is one of the significant genes reported to be involved in many metals’ toxicity , and showed a good dose–response relationship with mortality in our previous study . Another advantage is that for complex mixtures exposed to natural environments, it might be easier to determine one or a set of genes than to determine the internal residues of each mixture component, especially with the development of high-throughput genetic detection technologies. , …”
Section: Resultsmentioning
confidence: 83%
“…Impact of Cd, Cu, and the Mixture on Different Toxic End Points. The functional analyses of common DEGs showed that several pathways were highly relevant to the known toxic mechanisms of Cd and Cu exposure, 40 and we further performed confirmatory assays accordingly (Figure 3). The time-dependent functional analysis of transcriptomic data is also used as the Supporting Information on the mode of action (Figure S3).…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Adult zebrafish (Danio rerio) were purchased from the Institute of Hydrobiology, Chinese Academy of Sciences (Wuhan, China) and cultured in the laboratory as described in previous work. 62 Zebrafish were maintained in a tank with carbonfiltered dechlorinated tap water for 2 weeks to acclimate to laboratory conditions. The temperature was set at 26 ± 1 °C and the photoperiod of 12 h/12 h light/dark was implemented.…”
Section: Methodsmentioning
confidence: 99%